Map of Jordan governorates wind distribution and mean power density - S. Alrwashdeh, Saad (International Journal of Engineering and Technology, 2018)
The Renewable energy potential in Jordan is enormous as it lies within the top of the world countries renewable resources. Electricity demand in Jordan plays a major role in the high amount of energy requring to cover the needs of heating, cooling, lighting, etc. For that, the availability of the wind distribution information becomes essential to help in the design and building of the wind energy application. In this study, a wind distribution map is provided of all Jordan governorates: Irbid, Mafraq, Ajloun, Jarash, Amman, Zarqa, Madaba, Balqa, Karak, Tafilah, Mann and Aqaba.Â Â